Acute resistance exercise stimulates sex-specific dimeric immunoreactive growth hormone responses. Issue 3 (June 2015) - Luk, Hui Ying; Kraemer, William J.; Szivak, Tunde K.; Flanagan, Shawn D.; Hooper, David R.; Kupchak, Brian R.; Comstock, Brett A.; Dunn-Lewis, Courtenay; Vingren, Jakob L.; DuPont, William H.; Hymer, Wesley C.
Abstract: Purpose: We sought to determine if an acute heavy resistance exercise test (AHRET) would elicit sex-specific responses in circulating growth hormone (GH), with untreated serum and serum treated with a reducing agent to break disulfide-bindings between GH dimers. Methods: 19 untrained participants (nine men and ten women) participated in an acute heavy resistance exercise test using the back squat. Blood samples were drawn before exercise (Pre), immediate post (IP), + 15 min (+ 15), and + 30 min (+ 30) afterwards. Serum samples were chemically reduced using glutathione (GSH). ELISAs were then used to compare immunoreactive GH concentrations in reduced (+ GSH) and non-reduced (− GSH) samples. Data were analyzed using a three-way (2 sex × 2 treatment × 4 time) mixed methods ANOVA, with significance set at p  ≤ 0.05. Results: GSH reduction resulted in increased immunoreactive GH concentrations when compared to non-reduced samples at Pre (1.68 ± 0.33 μg/L vs 1.25 ± 0.25 μg/L), IP (7.69 ± 1.08 μg/L vs 5.76 ± 0.80 μg/L), + 15 min (4.39 ± 0.58 μg/L vs 3.24 ± 0.43 μg/L), and + 30 min (2.35 ± 0.49 μg/L vs 1.45 ± 0.23 μg/L). Also, women demonstrated greater GH responses compared to men, and this was not affected by reduction. Conclusions: Heavy resistance exercise increases immunoreactive GH dimer concentrations in men and women, with larger increases in women and more sustained response in men. The physiological significance of a sexually dimorphic GH response adds to the growing literature on aggregate GH and may be explained by differences in sex hormones and the structure of the GH cell network. Highlights: Heavy resistance exercise increases immunoreactive GH dimer concentrations in men and women. Women have larger increases in dimer concentrations while men have a more sustained response. The physiological significance of a sexually dimorphic GH response adds to the growing literature on aggregate GH. Differences may be explained by variances in sex hormones and the structure of the GH cell network.